The Influence of growth mindset and multiple intelligences on elementary students’ self-regulation - Nurul Zikri Filina; Tria Marvida; Dian Erlita; Lindayani Lindayani; Putri Fakhrina Sari (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study examines the association between ALEXISTOTO growth mindset, multiple intelligences, and elementary school students’ self-regulation. Self-regulation is a key competency in elementary education, yet it is often treated as a technical learning skill rather than an integrated cognitive and behavioral capacity. Using a quantitative explanatory design, the study involved 239 fifth-grade students from elementary schools in Aceh. Data on growth mindset, multiple intelligences, and self-regulation were collected through structured questionnaires and analyzed using multiple regression analysis. The results show that growth mindset and multiple intelligences together account for a substantial proportion of variance in students’ self-regulation (R² = 0.673, p < 0.001). Growth mindset was the stronger predictor (β = 0.678, p < 0.001), while multiple intelligences also showed a smaller but statistically significant association (β = 0.155, p = 0.024). These findings indicate that students with higher growth mindset scores and more developed multiple intelligences tend to report higher levels of self-regulation. The study provides empirical evidence on the relative contribution of growth mindset and multiple intelligences to self-regulation among elementary students, without implying causal relationships. The findings may inform educational practices aimed at supporting students’ self-regulatory development.